The response of tropical cyclone hazard to natural and forced patterns of warming - Jonathan Lin; Chia-Ying Lee; Suzana J. Camargo; Adam H. Sobel; Jing-Yi Zhuo (npj Climate and Atmospheric Science)
Abstract This study quantifies the influence of the pattern of sea surface temperature change in the tropical Pacific on tropical cyclone hazard. After downscaling a climate model with an “El Niño-like” forced response, it is found that the “El Niño-like” pattern of warming induces an “El Niño-like” change to tropical cyclone hazard. The magnitude of hazard change owing to the “El Niño-like” pattern of warming is estimated to be around the same order of magnitude as that driven by the forced response that does not project onto the same pattern of warming, highlighting the sensitivity of local tropical cyclone hazard to the pattern of warming. Given the uncertainty around the future pattern of Pacific warming, a storyline with a “La Niña-like” pattern of warming, of similar magnitude to the observations, is created. In this scenario, near-term tropical cyclone hazard over coastal Asia and the Atlantic basin significantly increases.